Post-Colonialism Perspective: Why Turkey's Efforts to Join EU always 'Go Down in Flames'? - Rizqullah, Muhammad Fawwaz Syafiq; Maulaya, Mahbi (Universitas Muhammadiyah Yogyakarta, 2021)
European Union (EU) is an economically advanced, politically reliable, socially progressive, and regionally integrated community, making the so-called 'the role model of world's regionalism' seem adorable in Turkey's lens. Having the opportunity to wave its flag in Brussels has been Turkey's foreign policy since 1987. Turkey's modus operandi to make the EU opening its door are enormous in scale. Yet, it does not mean that Turkey would quickly receive a lukewarm response from the EU. This paper lays down some theoretical arguments based on post-colonialism to discover why the EU has given a persistent rejection and derogation towards Turkey. As this paper stands in a post-colonialism stance, the Euro-centrism sense, which is embedded in the EU's way of thought, serves as the reason why intentional rejection is intensively addressed towards Turkey. This paper contains several features. After delivering a short introduction, there will be a modest explanation in picturing the used-theoretical framework. The discussion section stands upon three main questions; why does the EU treat Turkey differently from Greece? Is Turkey capable of fulfilling Copenhagen criteria? Does the EU tend to act in a discriminative manner to Turkey?